Prolonged Effects of Acute Stress on Decision-Making under Risk: A Human Psychophysiological Study - Yamakawa, Kaori; Ohira, Hideki; Matsunaga, Masahiro; Isowa, Tokiko (Frontiers in Human Neuroscience, 2016)
This study investigates the prolonged effects of physiological responses induced by acute stress on risk-taking in decision-making. Participants were divided into a Stress group (N = 14) and a Control group (N = 12). The Trier Social Stress Test was administered as an acute stressor, and reading was administered as a control task; thereafter, participants performed a decision-making task in which they needed to choose a sure option or a gamble option in Gain and Loss frame trials 2 h after (non-) exposure to the stressor. Increased cortisol, adrenaline, heart rate (HR), and subjective stress levels validated acute stress manipulation. Stressed participants made fewer risky choices only in the Gain domain, whereas no effect of stress was shown in the Loss domain. Deceleration of HR reflecting attention was greater for Gains compared with Losses only in the Stress group. Risk avoidance was determined by increased levels of cortisol caused by acute stress. These results suggest that processes regarding glucocorticoid might be involved in the prolonged effects of acute stress on the evaluation of risks and the monitoring of outcomes in decision-making.